PERSEPSI GURU TERHADAP PELAKSANAAN BIMBINGAN KARIR DI SEKOLAH DASAR: STUDI KUALITATIF DI SD GMIT 27 MEBUNG - Ayu Maubuthy; Naomi Pulamau; Adventia Korang; Yessy Mata; Petrus Mau Tellu Dony (CV. Adiba Aisha Amira, 2025)
This study aims to examine teachers' perceptions of the implementation of career guidance in elementary schools, specifically at GMIT 27 Mebung Elementary School, Alor Regency. The implementation of career guidance in elementary schools generally still faces various problems that hinder the achievement of objectives, such as teachers' limited understanding of the concept of early childhood career guidance, the lack of a systematic program, low parental involvement, and the absence of a dedicated guidance counselor at the elementary school level. Career guidance in elementary schools is not only an introduction to the world of work, but also contains educational values that support the development of students' potential, interests, and learning motivation from an early age. This study used a qualitative method, with a case study approach. Data collection techniques, namely participant observation and in-depth interviews to explore teachers' understanding regarding the implementation of career guidance services in the school environment. The data analysis technique used was descriptive qualitative analysis. The results of the study indicate that teachers have a positive perception of the importance of career guidance in elementary schools, although their understanding and practice are still simple and not systematically structured. Career guidance is not only provided through special services, but is also integrated into subjects and various school activities. In intracurricular activities, teachers link subject matter with career insights. Meanwhile, in extracurricular activities such as scouting, sports, and the arts, career guidance is implemented through skills training, creativity development, and the instilling of discipline. This research contributes to strengthening the role of teachers as facilitators of career development from an early age and serves as a reference for developing career guidance programs in elementary schools, particularly in the Alor Islands region.